Physicians' awareness in Yazd province about Biological Effects of ionizing radiation applied in radiological imaging procedures - Ali Chaparian; Hosain Hekmati moghadam; Mahsa Mansourian (Shahid Sadoughi University of Medical Sciences, 2014)
Introduction: Ionizing radiation has long-term risks, especially cancer. Since physicians request radiological examinations for patients, they need to be aware of its benefit and also risks. The aim of this study was to assess the overall knowledge of physicians in Yazd province about the radiation risks associated with diagnostic imaging procedures. Material and Methods: In this descriptive study a questionnaire containing 25 questions was used to evaluate physicians' knowledge of radiation doses received from radiological procedures and risks of cancer from diagnostic imaging. Their demographics such as age, sex, specialty and experience (years of practice) was also asked. Normality of data distribution was assessed using the Shapiro-Wilks test and the Kolmogorov-Smirnov test. A t-test was used for continuous variables and comparison of mean differences in scores for dichotomous variables. Spearman's correlation coefficient was carried out to look for any relationship between variables of age and experience with the knowledge of the physicians. Results: The overall mean knowledge score was 14 ± 3.15 out of 25 questions, or 56% ± 12.6%, and the scores ranged from 11.5% to 81%. The total mean score did not correlate with age and experience, but there was a significant difference (P value= 0.001) between men and women and also among the two main respondent groups, general practitioners and specialists (P value= 0.012). Physicians' knowledge about detrimental effects of radiation including both deterministic and stochastic effects was very weak. Conclusion: The awareness of physicians about radiation is generally inadequate. Adequate training to practicing physicians about risks of radiological examinations seems needed, and revision of the curriculum of medical students in this area is recommended.